ARABICA COFFEE PRODUCTIVITY IMPROVEMENT STRATEGY WITH VALUE CHAIN ANALYSIS APPROACH (CASE STUDY: SAPAN VILLAGE, NORTH TORAJA - Sapta Asmal; Syarifuddin Muhammad Parenreng; Widi Astutik (Center for Study and Journal Management FTI UMI, 2022)
Coffee is a farm commodity that has an important role in economic activities in Indonesia. The Indonesian coffee sector is dominated by small producers. North Toraja Regency, including in Sapan Village, is known as a producer of high quality coffee but low production. This study aims to examine the strategy of increasing coffee productivity in Sapan Village using value chain analysis. Data were collected through observation and interviews with cultivators in the value chain. This study shows that the productivity of coffee produced is still relatively low. The basic cause of low coffee productivity is that cultivation techniques are not good because information on good agriculture practices is still limited and there is a thought that the selling price of coffee is still low. To increase productivity, farmers need the role of the government. Farmers need counseling on coffee cultivation techniques that are in accordance with the application of GAP and price transparency from the government. If farmers have applied coffee cultivation techniques well, coffee productivity will increase so that farmers' income will also increase.